Cost Control Method and Software in Bidding Process Based on Gray System Forecast - Xi-Liu Zhou (Journal of Control Science and Engineering)
With the fast development of social economy, the competition between enterprises in construction projects becomes more and more serious. The cost control method is proposed to the bidding process of enterprises based on the gray system forecast. At the same time, the cost control software is also constructed to the bidding process of enterprises. Experimental results suggest that the proposed approach is feasible and correct.